2014
DOI: 10.1038/srep05002
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma matrix-metalloproteases (MMPs) and their polymorphisms (SNPs) in sepsis development and outcome in ICU patients

Abstract: Matrix-metalloproteases (MMPs) and their tissue-inhibitors (TIMPs), modulated by different single nucleotide polymorphisms (SNPs), are critical in sepsis development. Ninety ICU severely septic and 91 ICU uninfected patients were prospectively studied. MMP-1 (−1607 1G/2G), MMP-3 (−1612 5A/6A), MMP-8 (−799 C/T), MMP-9 (−1562 C/T), and MMP-13 (−77A/G) SNPs were genotyped. Plasma MMPs (-1, -2, -3, -8, -9, -10, -13) and TIMPs (-1,-2,-4) were measured. AA homozygotes and A allele carriers of MMP-13 (−77 A/G) and 1G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…Some studies have shown higher MMP-9 levels correlate with improved survival in severe sepsis (18)(19)(20), whereas other reports illustrate decreased survival with increased MMP-9 levels (21) or increased MMP-9 levels in septic patients without any clear effect on mortality (22). Recent attempts to clarify these discrepancies have compared the levels of various MMPs in septic patients with those of other intensive care unit patients admitted for noninfectious reasons such as stroke or trauma: results showed lower levels of MMP-9 in septic patients than trauma and stroke controls and no difference between septic survivors and nonsurvivors (23). While this data did not quell the controversy surrounding MMP-9 levels and septic prognosis, it did highlight the need for further exploration of the role and mechanisms through which MMPs contribute to the pathophysiology of sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies have shown higher MMP-9 levels correlate with improved survival in severe sepsis (18)(19)(20), whereas other reports illustrate decreased survival with increased MMP-9 levels (21) or increased MMP-9 levels in septic patients without any clear effect on mortality (22). Recent attempts to clarify these discrepancies have compared the levels of various MMPs in septic patients with those of other intensive care unit patients admitted for noninfectious reasons such as stroke or trauma: results showed lower levels of MMP-9 in septic patients than trauma and stroke controls and no difference between septic survivors and nonsurvivors (23). While this data did not quell the controversy surrounding MMP-9 levels and septic prognosis, it did highlight the need for further exploration of the role and mechanisms through which MMPs contribute to the pathophysiology of sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 93%
“…We did not perform any power analysis due to missing pre-study data. The sample of 53 septic patients was assessed to be adequate based on previous MMP-9 and TIMP1studies in other septic patient populations (Muhl et al 2011;YazdanAshoori et al 2011;Martin et al 2014). The normality of data was assessed with Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a number of SNPs have been described for a number of MMPs [12]. A recent paper reported SNP in the MMP9 gene promoter that reduces the risk of diabetic microvascular complications [13], but there is no study specifically examining MMP9 SNPs in DN.…”
Section: Introductionmentioning
confidence: 99%